A Equação de Codazzi em superfícies - Santos, Maria Rosilene Barroso dos (2011)
In this work, based on the article The Codazzi Equation for Surfaces by Juan A. Aledo, José M. Espinar and José A. Gálvez [8], we describe some applications of an abstract theory for the Codazzi equation on surfaces. This theory deals with abstract pairs of quadratic forms on a surface, in particular the so-called Codazzi pairs, for which the Codazzi equation is satisfied. Among the applications, we give a proof of an abstract version of a classical theorem due to Hopf on immersed spheres in Euclidean space R3 with constant mean curvature. Other applications are proofs of Liebmann s theorem on complete surfaces with constant Gaussian curvature in R3 and of Grove s theorem on the rigidity of ovaloids. We also study the existence of holomorphic quadratic differentials associated with Codazzi pairs. This is used, in particular, in the classification of complete embedded elliptic special Weingarten surfaces of non-minimal type in R3 whose Gaussian curvature does not change sign.